2011
DOI: 10.1186/cc10252
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timing of renal replacement therapy initiation on outcome of septic acute kidney injury

Abstract: IntroductionSepsis is the leading cause of acute kidney injury (AKI) in critical patients. The optimal timing of initiating renal replacement therapy (RRT) in septic AKI patients remains controversial. The objective of this study is to determine the impact of early or late initiation of RRT, as defined using the simplified RIFLE (risk, injury, failure, loss of kidney function, and end-stage renal failure) classification (sRIFLE), on hospital mortality among septic AKI patients.MethodsPatient with sepsis and AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 46 publications
3
78
2
6
Order By: Relevance
“…Without this, no conclusion regarding the effectiveness of dialysis versus nondialysis can be made. In general, studies examining patients dialyzed at a high creatinine versus those dialyzed at a low creatinine have demonstrated that outcomes are better when dialysis is initiated at a higher creatinine concentration (20,(22)(23)(24)(25). Our results confirm and expand upon those seen in prior studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Without this, no conclusion regarding the effectiveness of dialysis versus nondialysis can be made. In general, studies examining patients dialyzed at a high creatinine versus those dialyzed at a low creatinine have demonstrated that outcomes are better when dialysis is initiated at a higher creatinine concentration (20,(22)(23)(24)(25). Our results confirm and expand upon those seen in prior studies.…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies examining the initiation of dialysis for AKI have not generated consensus (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Significantly heterogenous, these studies fail to include an adequate nondialyzed control group.…”
Section: Discussionmentioning
confidence: 99%
“…Shiao et al (2009) reported that the RIFLE criteria were useful in predicting post-AKI mortality; however, Chou et al (2011) stated that the RIFLE criteria were not associated with the mortality of critically ill patients with AKI. In our study, we noted that the AKIN stage (stage 2: HR, 0.819; 95% CI, 0.527-1.273; stage 3: HR, 1.277; 95% CI, 0.945-1.725; reference, stage 0 or 1) was not associated with the risk of mortality after AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Manche [17] 2008 IHD Cardiac surgery Hyperkalemia Urine output <0.5mL/kg/h Iyem [18] 2009 CVVH Cardiac surgery RRT on admission After 48 h when anuric Shiao [19] 2009 CVVH Surgery/trauma RIFLE criteria (risk) RIFLE injury (failure) Carl [20] 2010 CRRT/IHD Medical (sepsis) Urea <35.7 mmol/L Urea >35.7 mmol/L Chou [21] 2011 CRRT/SLED Sepsis RIFLE criteria (risk) RIFLE injury (failure) García-Fernández [22] 2011 CRRT/IHD Cardiac surgery ≤3 days after cardiac surgery >3 days after cardiac surgery Note: RIFLE Criteria (Risk): Increase in serum creatinine by 1.5 times or urine output <0.5 mL/kg/h × 6 h; RIFLE Criteria Injury: Increase in serum creatinine by 2 times or urine output <0.5 mL/kg/h × 12 h; RIFLE Criteria (Failure): Increase in serum creatinine by 3 times or urine output <0.3 mL/kg/h × 24 h. the definition of "early" and "late" RRTs. Patients in seven studies 2,3,[13][14][15]18,19 used CRRT and patients in two studies 10,17 used IHD.…”
Section: On Admission At 24 Hmentioning
confidence: 99%